Detection of Antigen-Specific T Cells Using In Situ MHC Tetramer Staining - Abdelaal, Hadia M.; Cartwright, Emily K.; Skinner, Pamela J. (International journal of molecular sciences, 2019)
The development of in situ major histocompatibility complex (MHC) tetramer (IST) staining to detect antigen (Ag)-specific T cells in tissues has radically revolutionized our knowledge of the local cellular immune response to viral and bacterial infections, cancers, and autoimmunity. IST combined with immunohistochemistry (IHC) enables determination of the location, abundance, and phenotype of T cells, as well as the characterization of Ag-specific T cells in a 3-dimensional space with respect to neighboring cells and specific tissue locations. In this review, we discuss the history of the development of IST combined with IHC. We describe various methods used for IST staining, including direct and indirect IST and IST performed on fresh, lightly fixed, frozen, and fresh then frozen tissue. We also describe current applications for IST in viral and bacterial infections, cancer, and autoimmunity. IST combined with IHC provides a valuable tool for studying and tracking the Ag-specific T cell immune response in tissues.